2021
DOI: 10.1111/jcpe.13452
|View full text |Cite
|
Sign up to set email alerts
|

De‐epithelialized gingival graft versus subepithelial connective tissue graft in the treatment of multiple adjacent gingival recessions using the tunnel technique: 1‐year results of a randomized clinical trial

Abstract: Aim To compare the clinical efficacy and postoperative morbidity of de‐epithelialized gingival graft (DGG) with subepithelial connective tissue graft (SCTG) on treatment of multiple adjacent gingival recessions (MAGRs) with tunnel technique (TUN) and to evaluate histological characteristics of the palatal grafts. Materials and methods Twenty‐seven patients with MAGRs affecting at least 2 adjacent teeth were treated with either DGG + TUN or SCTG + TUN. Recession depth(RD) and width(RW), probing depth(PD), clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 38 publications
2
21
5
Order By: Relevance
“…Nonetheless, single linear measurements (recession height and width) did not emerge as potential prognostic parameters of statistically significant importance in our report. The findings of the present study are not in line with results from a recently published study by Bakhishov et al [ 39 ] who found in multilevel regression analysis that GR height at baseline was a significant negative prognostic factor in the amount of 12-month ARC after MCAT + SCTG (p = 0.02). The mentioned model revealed no significant effect of initial RW on ARC though, which was in accordance with our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Nonetheless, single linear measurements (recession height and width) did not emerge as potential prognostic parameters of statistically significant importance in our report. The findings of the present study are not in line with results from a recently published study by Bakhishov et al [ 39 ] who found in multilevel regression analysis that GR height at baseline was a significant negative prognostic factor in the amount of 12-month ARC after MCAT + SCTG (p = 0.02). The mentioned model revealed no significant effect of initial RW on ARC though, which was in accordance with our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Azar et al [31] reported that, DGG could be considered as "dense CTG", included minimum adipose and epithelial tissue. Despite epithelial remnant cells during de-epithelialization [32], DGG was unique graft for root coverage [18].…”
Section: Discussionmentioning
confidence: 99%
“…Using DGG has minimized chair time during operation was recorded [17]. Implementation DGG with tunnel technique in the treatment of gingival recessions was successfull [18], many alternative products as connective tissue grafts (CTG), collagen matrix [19], acelular dermal allo-and xenografts [20] have been studied. In spite of many articles, few articles have discussed using DGG for multiple recessions, especially when associated with the tunnel technique [18,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct modifications to the original tunnel technique have been described over time by several authors to improve clinical outcomes [6][7][8]. Although the efficacy of the tunnel technique was dependent on the application of subepithelial connective tissue graft (SCTG), which was regarded as the gold standard [9], attempts have been made to search for materials alternative to SCTG, such as collagen porcine dermal matrix [10], enamel matrix derivatives [11], and concentrated growth factors [12]. In order to achieve good esthetic results, the understanding how to apply scientific evidence for a given case is crucial [13].…”
Section: Introductionmentioning
confidence: 99%